Methods of evaluation of occlusal contacts in orthodontic patients – review of literature - Piątek-Jakubek, Katarzyna; Motyl, Sylwia; Williams, Stephen; Loster, Bartłomiej (Journal of Stomatology, 2017)
Introduction. The assessment of occlusal contacts before and after orthodontic treatment is important in the light of the evaluation of the therapeutic effects. Functional stability is ensured, first and foremost, by good intercuspation, with many, properly localized occlusal contacts. Aim of the study. To present methods of registration and evaluation of occlusal contacts and to summarize conclusions from the literature on the analysis of occlusal contacts in an orthodontic patient. Material and methods. PubMed, EBSCOhost, Science Direct and Google Scholar were searched for the literature of the subject by entering the following keywords: occlusal contacts analysis, occlusal contacts orthodontic treatment, occlusion indicators, occlusion recording materials. Thirty-three articles were analyzed. Results. For the registration of occlusal contacts, qualitative methods (wax, silicone, an articulating paper, a foil, a silk strip) as well as quantitative ones (photoocclusion technique, T-scan) are used. It is important to use simple and reliable methods of recording the results of occlusion tests to assess the changes that occur. Two-dimensional methods (e.g. description, photo, scheme or computer drawing) or three-dimensional ones (e.g. virtual models) may be mentioned. In the retention phase, there is a dynamic change in occlusal contacts. There is a significant increase in the number of ideal occlusal contacts, but the number of incorrectly located contacts is also increasing. Therefore, it is believed that settling should take place in the last phase of active orthodontic treatment. Evaluation of the number and location of occlusal contacts may be the most important predictor of occlusion stability and may be helpful in explaining the relapse, should this happen in the future. Conclusion. The evaluation of occlusal contacts, although very important, is not commonly used in orthodontic practice. There is no “gold standard” for marking, recording and evaluation of occlusal contacts.